(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Nursing is an honorable profession that calls for a rare blend of scientific knowledge andhumane concern. Empathy is crucial to nursing because it helps nurses to form meaningful relationshipswith their patients and provide them all-encompassing care when they are at their most vulnerable anddistressed. In order to determine whether or not a nursing student is qualified to provide patient-centeredcare and promote good healthcare experiences, it is important to understand and measure their levels ofempathy. In the field of nursing, empathy is the capacity to identify with and care about the experiencesand circumstances of one’s patients, their loved ones, and one’s peers. It entails putting oneself in thepatient’s shoes in order to better understand their worries and concerns and actively listening to themwithout passing judgment. Increased patient satisfaction and better health outcomes may be achievedvia the efforts of highly empathic nurses who establish rapport, calm fears, and promote open lines ofcommunication. The purpose of this study was to analyze the interns’ perceptions of their own degree ofempathy. Descriptive and cross-sectional in approach, this research. The mean empathy score of thenursing interns in this research was 67.46 (SD = 18.86). This finding suggested that the nursing interns’empathy was around average.